Development and validation of RP-HPLC method for simultaneous estimation of paracetamol and chlorzoxazone in bulk form - Hajera N. Khan; Mahajan Swarali; Chopde Asha; Mohammad Zameeruddin; Vishvanath B. Bharkad (International Journal of Pharmacy and Analytical Research, 2022)
High performance liquid chromatography (HPLC) method was developed and validated for the analysis of Paracetamol and Chlorzoxazone. Chromatographic separation achieved isocretically on C -18 column Zorbax Eclipse XDB- C18 (4.6 250mm 5µ). Utilizing a mobile phase Acetonitrile: Water in the ratio 50:50v/v. with a flow rate of 1.5ml/min. UV detection was carried o ut at 274nm. The retention time of Paracetamol and Chlorzoxazone <10 min respectively. The developed method was validated in terms of recovery, precision, rggedness, robustness, linearity as per ICH guidelines. This study aimed at developing and validating an HPLC method.